Performance Measurement System and Business Lending Efficiency at Cooperative X in Rembang Regency - Ayun, Annisa Qurrota; Prayogo, Imam; Wildan, Muhammad; Pugara, Ade; Dwianto, Agus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose The purpose of this study is to evaluate Cooperative X in Rembang's business credit efficiency and performance measurement system. Internal control officers (ICOs) in their capacity as auditors are the study's subjects. Methodology: This is an experimental study that collects data in addition to employing a convenience sample technique. 92 questionnaires were distributed in Cooperative X in Rembang City to gather data. Answers were given by 58 former internal control officers, 12 risk managers, and 22 internal auditors out of the 92 interviewees (53%). Structural equation modeling data analysis looks at the link between latent and observable variables. Findings: According to the results of the hypothesis test, the performance assessment system is significantly impacted by credit performance. The effectiveness of credit has a big impact on management control. Loan performance has a significant Organisational learning is significantly impacted by lending performance. Employee sentiments are significantly impacted by lending performance. Applications/Originality/Value: This study examines the role of the Management Control System (MCS), especially the Performance Measurement System (PMS), in improving the lending (credit) performance of Cooperative X in Rembang. The research will be discussed and aims to determine whether the relationship between the Management Control System (MCS) and Attitudes toward risk and organizational learning can be used to explain lending (credit) performance (balanced scorecard equal).